2020
DOI: 10.1177/0022219420915867
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot of RTI Implementation a Decade Later: New Picture, Same Story

Abstract: Response to intervention (RTI) has evolved from its first decade of implementation. Because states guide and regulate policy and practice at the state and local education agency levels, it is important to understand their critical role in RTI implementation. A systematic review of all 50 state education agency websites was conducted to provide an updated “snapshot” of states’ interpretation of RTI a decade after IDEA regulations were finalized. Findings revealed substantive progress towards developing approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…RTI frameworks and multitiered systems of support (MTSS), established in school systems (Berkeley et al., 2020), are frameworks practitioners may use to identify students with LD, MLD, and MD. Typically, students are defined as having MD if they need additional support in mathematics despite being included in the general education curriculum, whereas LD is defined as levels of progress that are incommensurate with the amount of intervention implemented throughout a system of increasingly intensified instructional support (Elias, 2021).…”
Section: Foci Of Syntheses Of Mathematics Interventionsmentioning
confidence: 99%
“…RTI frameworks and multitiered systems of support (MTSS), established in school systems (Berkeley et al., 2020), are frameworks practitioners may use to identify students with LD, MLD, and MD. Typically, students are defined as having MD if they need additional support in mathematics despite being included in the general education curriculum, whereas LD is defined as levels of progress that are incommensurate with the amount of intervention implemented throughout a system of increasingly intensified instructional support (Elias, 2021).…”
Section: Foci Of Syntheses Of Mathematics Interventionsmentioning
confidence: 99%
“…Syntheses of single-case investigations are also commonly performed to identify empirically supported practices for school adoption Peltier et al, 2020). In its most basic application, single-case investigations are similar to the way academic or behavioral progress monitoring data are collected in response to intervention (RTI; Berkeley et al, 2020;Furey & Loftus-Rattan, 2022) and multitiered systems of supports (MTSS; National Center on Intensive Intervention, 2020). Thus, aspects of single-case research may be familiar to doctoral students who work in inclusive schools that utilize tiered systems of student support (see Berkeley et al., 2020;McKenna et al, 2021).…”
Section: Single-case Designmentioning
confidence: 99%
“…Of those who reported using RTI or MTSS, most participants reported using a failure to benefit from Tier 2 instruction (91.4%, n = 371), whereas about half reported using a failure to benefit from Tier 1 (48.0%, n = 195), and few participants reported using failure to respond to Tier 3 (4.2%, n = 17). It can be challenging to interpret these results, given that the definition of tiers within RTI/MTSS systems differs at the state level, however, Tier 1 traditionally represents whole-class instruction, whereas Tier 2 typically consists of small-group instruction and Tier 3 may represent small-group instruction, individualized instruction, or special education depending on the context (Berkeley et al, 2020). A majority of those who indicated using a standard deviation below the mean reported that students needed to score below the cutoff on multiple measures (90.2%, n = 248), whereas some indicated using a cutoff score on one measure (29.8%, n = 82).…”
Section: Q3 Measures and Procedures Used To Identify Rdsmentioning
confidence: 99%